Weaker implicit interoception is associated with more negative body image: Evidence from gastric-alpha phase amplitude coupling and the heartbeat evoked potential. (October 2021) - Todd, Jennifer; Cardellicchio, Pasquale; Swami, Viren; Cardini, Flavia; Aspell, Jane E.
Abstract: Interoception refers to the processing of internal bodily stimuli, while body image refers to appearance-related perceptions, affect, and cognitions. Previous research has found that body image is associated with self-reported and behavioural indices of interoception. Here, we extended this research by examining associations between measures of positive (i.e., body appreciation, functionality appreciation) and negative body image (i.e., body shame, weight preoccupation) and two electrophysiological indices of interoceptive processing, namely the heartbeat evoked potential (HEP) and gastric-alpha phase-amplitude coupling (PAC), in a sample of 36 adults. Significant negative associations were identified between the indices of negative body image and the interoception variables. Specifically, more negative HEP amplitude and lower gastric-alpha PAC were both associated with greater body shame and weight preoccupation. However, no significant associations were identified for the indices of positive body image. These findings extend previous work by demonstrating that there are significant associations between negative body image and previously unexplored components of cardiac and gastric interoception. This, in turn, could have important clinical applications, such as the HEP and gastric-alpha PAC both serving as biomarkers of negative body image.